2012 IEEE 7th Sensor Array and Multichannel Signal Processing Workshop (SAM) 2012
DOI: 10.1109/sam.2012.6250480
|View full text |Cite
|
Sign up to set email alerts
|

Range bias modeling for hyperbolic frequency modulated waveforms in target tracking

Abstract: Abstract-Hyperbolic frequency modulated (HFM) waveforms offer detection performance that is "Doppler insensitive"-relatively unaffected by target range-rate in matched filtering. They have been applied in radar; but more they are particularly useful in sonar where the wideband Doppler insensitivity is especially prized. However, Doppler insensitivity does come hand in hand with a range bias, which would significantly degrade the tracking performance. In this paper, we model the range bias as a function of rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Consequently, for such IDTs both the electrode and gap centers' positions must be determined and only then electrode's width with a fixed metallization ratio can be calculated. In the first approximation, the electrode and the positions of gap centers are determined from the required impulse response s(t) which corresponds to ideal theoretical HFM waveforms such as [13], where the signal acquires pure real and imaginary values (signal phase is k and 2…”
Section: Design Of Hfm Transducersmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, for such IDTs both the electrode and gap centers' positions must be determined and only then electrode's width with a fixed metallization ratio can be calculated. In the first approximation, the electrode and the positions of gap centers are determined from the required impulse response s(t) which corresponds to ideal theoretical HFM waveforms such as [13], where the signal acquires pure real and imaginary values (signal phase is k and 2…”
Section: Design Of Hfm Transducersmentioning
confidence: 99%
“…Based on the HFM waveforms instantaneous frequency -time dependence presented in [13], the instantaneous frequency delay of the ideal HFM signal is expressed as…”
Section: Evaluation Of Hfm Transducer Characteristicsmentioning
confidence: 99%
“…2) Doppler Compensation Using Chirps With Hyperbolic Frequency Modulation: In [44], it is shown that hyperbolicfrequency modulated (HFM) chirps have an optimal modulation property or Doppler invariance which was already derived in [45] and [46]. The HFM chirp is given by…”
Section: ) Doppler Compensation Of An Lfm Signalmentioning
confidence: 99%
“…During the past decades, specialists and scholars have made huge contributions to the research on the cross ambiguity function (CAF) [1][2][3], especially in the presence of Gaussian noise. A linear canonical transform was introduced to ambiguity function for the time-frequency analysis of the cubic phase signal in [4].…”
Section: Introductionmentioning
confidence: 99%